Innate immunity, therapeutic targets and monoclonal antibodies in SARS-CoV-2 infection - Mubashir Nazir; Ishfaq Rashid Mir; Shabir Ahmad Lone; Ghazala Muteeb; Ragib Alam; Anis Bashir Fomda; Nida Khan; Asim Azhar; Bashir Ahmad Fomda; Wajihul Hasan Khan (PeerJ)
COVID-19 (coronavirus disease 2019), caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), stands as one of the most severe pandemics the world has ever faced in recent times. SARS-CoV-2 infection exhibits a wide range of symptoms, varying from severe manifestations to mild cases and even asymptomatic carriers. This diversity stems from a multitude of factors, including genetic predisposition, viral variants, and immune status. During SARS-CoV-2 infection, the immune system engages pattern recognition receptors, setting off a series of intricate signalling cascades. These cascades culminate in the activation of innate immune responses, including induction of type I and type III interferons. The emerging variants of SARS-CoV-2 pose challenges to the innate immune system defense. Therefore, investigating the innate immune response is crucial for effectively combating SARS-CoV-2 and its variants. The cyclic guanosine monophosphate-adenosine monophoshate synthase-stimulator of interferon genes (cGAS-STING) pathway, a critical innate immune mechanism, represents a promising target for intervention at multiple stages to reduce the severity and progression of SARS-CoV-2 infection. This review explores innate immunity in SARS-CoV-2 infection and other immune responses critical for SARS-CoV-2 defence. As part of the therapeutic approach, we extend our review to highlight monoclonal antibodies (mAbs) as emerging and effective therapeutics for controlling SARS-CoV-2 by targeting different stages of the innate immune system. A diverse range of mAbs has been explored to address specific targets within the innate immune pathways. A deep understanding of innate immunity and targeted monoclonal therapeutics will be instrumental in combating viruses and their variants, laying the foundation for enhanced treatment and therapeutic strategies.